Autoimmune cytopenias in patients with chronic lymphocytic leukaemia treated with ibrutinib in routine clinical practice at an academic medical centre. (16th August 2018) - Hampel, Paul J.; Larson, Melissa C.; Kabat, Brian; Call, Timothy G.; Ding, Wei; Kenderian, Saad S.; Bowen, Deborah; Boysen, Justin; Schwager, Susan M.; Leis, Jose F.; Chanan‐Khan, Asher A.; Muchtar, Eli; et al.
Summary: The effects of ibrutinib on the natural history of autoimmune cytopenias (AIC) among chronic lymphocytic leukaemia (CLL) patients treated in routine clinical practice require further investigation. Using the Mayo Clinical CLL Database, 193 CLL patients treated with ibrutinib between November 2013 and January 2017 outside the context of a clinical trial were identified; complete review of their medical records was performed for details of past history of AIC and treatment‐emergent AIC. We identified 29/193 (15%) patients with history of AIC prior to ibrutinib start. Of 12 patients requiring AIC therapy at ibrutinib start, 8 (67%) were able to discontinue or de‐escalate AIC treatment, and no patient had worsening of their AIC after initiating ibrutinib. Eleven (6%) patients developed treatment‐emergent AIC after a median of 59 (range, 6–319) days following the initiation of ibrutinib, 7 of whom (64%) were able to continue ibrutinib. Overall and event‐free survival from time of ibrutinib start were not significantly different between patients with history of AIC and those with no history of AIC. Treatment‐emergent AIC were seen exclusively in patients with unmutated IGHV and were associated with a shorter EFS. These results suggest a low rate of treatment‐emergent AIC and improvement in patients with existing AIC.